Natural Borneol Enhances Paclitaxel‐Induced Apoptosis of ESCC Cells by Inactivation of the PI3K/AKT. Issue 5 (16th April 2018) - Meng, Xiaofeng; Dong, Xiaomei; Wang, Wen; Yang, Liu; Zhang, Xia; Li, Yanfang; Chen, Tianfeng; Ma, Hang; Qi, Da; Su, Jianyu
Abstract : Abstract: Paclitaxel (PTX) has been used in a variety of malignancies for inhibiting tumor development and improving survival. However, its clinical application is limited due to poor solubility, drug resistance, and gastrointestinal reactions. Natural borneol (NB), as a promoter, could help to improve drug absorption. Therefore, the aims of the present study were to investigate the ability of NB to synergize with PTX to induce human esophageal squamous cell carcinoma (ESCC) cells apoptosis and the underlying mechanism of synergistic effects. In this study, our findings showed that NB could effectively synergize with PTX to inhibit the survival of ESCC cells by inducing apoptosis. The molecular mechanism by western blotting elucidated that combination treatment with PTX and NB significantly activated apoptotic pathway by triggering upregulation of cleaved caspase‐3 expression and downregulation of survivin and P‐AKT expression. These results demonstrated that NB could strongly potentiate PTX‐induced apoptosis in ESCC cells through suppressing PI3K/AKT pathway. Thus, the combination therapy with NB and PTX might be a promising treatment strategy for human esophageal cancer. Practical Application: Esophageal cancer is one of the most common cancers in the world. It has brought about a major public health problem. Many natural agents have been employed in the synergized treatments of esophageal cancer. This study provides a comprehensive way to investigate the ability of borneol to synergize with paclitaxel to induce human esophageal squamous cell carcinoma cells apoptosis and the underlying mechanism of synergistic effects. The research showed that the combination treatment with some natural agents might be a promising treatment strategy for human esophageal cancer.